Uogólnienie Problemu Gwozdiewa Nośności Granicznej Rur Cienkościennych na Przypadek Działania Ciśnienia Wewnętrznego - Skrzypek, J.; Życzkowski, M. (Engineering Transactions, 1970)
The problem of limit carrying capacity is solved of a thinwalled tube under the simultaneous action of internal pressure, axial force, two bending moments, two shear forces and torque. This is a direct generalization of A. Gvozdev’s solution to the case of the appearance of internal pressure. The applied variational approach consisting of extremization of the functional (2.12) - (2.13) leads here as a rule to kinematically admissible solutions (and simultaneously to statically partially admissible). Only in certain simple cases of loads (pressure, tension, twisting), when the condition of internal equilibrium (2.3) is satisfied, it does constitute an exact solution. Reduction of the general integral formulae (3.15) to the normal elliptical integrals is illustrated by an example.